Estudo do consumo hídrico em atividade de lavagem de pátio contendo sólidos por descarga de água de reservatório - Camargo, Bene Eloi Mendes (Universidade Federal de São Carlos, 2023)
The water’s individual measurement is the way in which society has seen the possibility of acting with a resource’s rational management. The main tool on this front is the hydrometer, but the cost of installing this equipment for large-scale flows and larger diameter pipes makes it unfeasible to disseminate the tool for localized measurement. In this sense, it is opportune to study and develop alternative techniques for measuring flow, so that the present work meets this theme. The flow measurement technique was chosen by varying the water level in the reservoir, with subsequent simulation of data in an electronic spreadsheet, taking observed data as a reference, and with the aim of subsidizing the operational routine of a conventional activity found in the field, and also in urban areas, which is the washing of a yard containing solids from animal excretion. The objective of this project was to study a system for measuring water consumption in reservoirs based on the measurement of the variation in the water level and simulate its behavior to study criteria for stopping the discharge of the reservoir in the case of cleaning the livestock yard. This research is justified by obtaining knowledge about how a non-conventional way of measuring water consumption can be applied in an activity found in the field, with the advantage of having a lower cost when compared to a conventional way of measuring, which is the measurement using hydrometers. Diversification in measurement converges with current needs, aiming to stipulate clear criteria, so that it is possible to measure and rationalize water consumption in activities, directing them towards sustainable performance. An ultrasonic distance sensor was studied to measure the performance of the level variation inside a reservoir in order to study the flow. The flow inferred by the sensor was validated by mass method. Based on the discharge behavior of the reservoir on a pilot scale and some principles that govern the dynamics of the dragging of solids that are deposited on surfaces, simulations were carried out to define criteria that provide minimum conditions for cleaning the yard for livestock activities. The ultrasonic distance sensor presented results that were adjusted by the boxplot normalization method, thus being able to be modeled. The simulation showed reservoir discharge behavior outlining volume batches and fixed time intervals. A simulation of the criterion for stopping the discharge of the reservoir for cleaning the yard was also obtained, the minimum water column of 0.45 m in a reservoir of 4 m of water column. Simulations can offer support material for the rational management of water resources.
Study of water consumption in yard washing activity containing solids by discharging water from a reservoir
Keywords: Nível d’água; Sensor ultrassônico; Critério de parada; Arraste de sólidos; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO; 6. Água Potável e Saneamento